Analysis of Work Ethics, Work Discipline, and Work Motivation on Employee Performance at PT Ghalia Creative Indonesia - Puji Adittya Efendi; Ahmad Aswan Waruwu; Wilchan Robain (Journal of Research in Social Science and Humanities, 2025)
This study aims to identify and analyze the effects of work ethics, work discipline, and work motivation on employee performance at PT Ghania Creative Indonesia. The research employs a quantitative method, with data analysis conducted using multiple linear regression. The sample consists of 46 respondents, selected through a non-probability sampling technique using saturated sampling. The results of the partial tests indicate that: (1) work ethics have a positive and significant effect on employee performance, with a calculated t value (2.247) greater than the t table value (1.68195) and a significance value of 0.030 0.05; (2) work discipline has a positive and significant effect on employee performance, with a calculated t value (3.274) greater than the t table value (1.68195) and a significance value of 0.002 0.05; and (3) work motivation has a positive and significant effect on employee performance, with a calculated t value (2.888) greater than the t table value (1.68195) and a significance value of 0.006 0.05. Simultaneously, work ethics, work discipline, and work motivation have a positive and significant effect on employee performance at PT Ghania Creative Indonesia, with a calculated F value (81.825) greater than the F table value (2.83) and a significance value of 0.000 0.05. The coefficient of determination (Adjusted R Square) indicates that 84.3% of employee performance is explained by work ethics, work discipline, and work motivation, while the remaining 15.7% is influenced by other factors not examined in this study